Here are some of the questions of the chapter **Polynomials** that I am getting confused with. Please make some efforts answering my questions. *Thanks!*

If \({ (x-1) }^{ 2 }\) is a factor of \(f\left( x \right) ={ x }^{ 3 }+bx+c\),then find the remainder when \(f\left( x \right)\) is divided by \(x-2\)

If \((x-p)\) and \((x-q)\) are the factors of \({ x }^{ 2 }+px+q\), then find the value of \(p\) and \(q\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestIn Question 1 you can use the fact that when a polynomial have identical roots there differentiation also have the same root.Which means that f'(x) will also have (x-1) as a root. @Swapnil Das

Log in to reply

Bhai mere Karl mera polynomial chapter ka test hai. Agar main wahan Calculus use karunga to anda milega !

Log in to reply

Extra marks for using calculus.

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Well, do try using calculus and see the response of ur teacher. He'll be proud of u!

Log in to reply

Nahi Milega.😐😑😑😑😑😑

Log in to reply

Since no one has posted the easiest solution I will.

We know the sum of roots is -b/a which in this case = 0.

We also know 2 roots are 1 hence the other root must be -2.

So the polynomial will be p(x) = (x-1)(x-1)(x+2).

@satvik pandey @Kalash Verma @Swapnil Das @Sravanth Chebrolu

Log in to reply

Remainder when we divide \(f(x)\) by \((x-1)^{2}\) is zero. Therefore \(-1=b+c\).

Now remainder when \(f(x)\) is divided by \(x-2\) is \(8+2b+c\) i.e \(7+b\).

Now we know by factor theorem that \(f(x)=(x-1)^{2}*q(x)\).

\(q(x)\) must be linear so let \(q(x)=x-z\).

Therefore \(f(x)=(x-1)^{2}(x-z)\)

Now \(x^{3}+bx+x=x^{3}-2x^{2}+x-zx^{2}+2xz-z\)

Comparing quadratic terms coef on both sides we get \(-(2+z)=0\) i.e \(z=-2\).

Now we compare linear terms we get \(b=1+2z=1+2*(-2)=1-4=-3\)

Therefore our remainder is \(7+b=7-3=4\).

Log in to reply

For the first question, we find that \(\dfrac{f(x)}{(x-1)^{2}}=0\). So dividing the polynomial, we find that:

For the remainder to be \(0\), we must have, \((b-1)x= -4x\) and \(c=2\). Hence we find that \(b=(-3)\) and \(c=2\).

So the polynomial will become, \(x^3-3x+2\).

Now, using remainder theorem, we find that the remainder of the polynomial is \(f(2)=2^3-(3×2)+2 \\ = 8-6+2 \\= \boxed {4}\)

I just wanted to show the other way of doing this. Hope you found it useful!\(\huge \ddot\smile\)

Log in to reply

Hi Swaplin, what are the answers?

Log in to reply

Well I even donno, I wish someone could help, :(

Log in to reply

The polynomial is of degree 3 so it should have three roots two of them are 1,1. Let the othe root be \(\alpha\).

So \(f(x)=(x-1)(x-1)(x-\alpha)=x^3-x^2(\alpha+2)+x(2\alpha+1)-\alpha\)

As coefficient of \(x^2\) must be zero so \(\alpha=-2\). Now using this you can form polynomial and then find remainder by remainder theorem.

2nd problem.

As the polynomial is of degree 2 so it should have 2 roots.

So \(f(x)=(x-p)(x-q)=x^2-(p+q)x+pq\)

So \(x^2-(p+q)x+pq=x^2+px+q\)

So \(-(p+q)=p\) and \( pq=q\)

Solve these simultaneous equations.

Please check the calculation. I am not very good at it. :P

Log in to reply

Log in to reply

Log in to reply

Log in to reply

@Sravanth Chebrolu for your help.

I am grateful to you andLog in to reply

Log in to reply

Log in to reply

Don't fear when

Brilliant.orgis here!Log in to reply

Log in to reply

LOL! Swaplin :P :P

Log in to reply

Lol

Log in to reply

I guess that it is Swap

nilLOL!Log in to reply

Please reshare the note and help me! @satvik pandey

Log in to reply